Thermochemical depolymerization of lignin: Process analysis with state-of-the-art soft ionization mass spectrometry - Zhu, Linyu; Cui, Cunhao; Liu, Haoran; Zhou, Zhongyue; Qi, Fei (Frontiers in Chemical Engineering, 2022)
Lignin valorization via thermochemical approaches has the potential to produce renewable fuels and value-added chemicals, which are of great significance to the sustainable development of human beings. During the thermochemical depolymerization which involves acid-catalyzed, alkali-catalyzed, oxidative, reductive, pyrolytic, and other reactions, the lignin structure will undergo a series of bond cleavage, condensation, and functional group changes, while the mechanism is still unclear. To improve the efficiency, the analysis of the evolution of intermediates during depolymerization is very important, among which soft ionization mass spectrometry plays a vital role. This review aims to summarize the research progress of process analysis of lignin depolymerization in both gas-phase, typically thermal and catalytic pyrolysis, and liquid-phase via online mass spectrometry. The challenges and our insights into the future development of the lignin valorization as well as soft ionization mass spectrometry methods are also discussed.